2020
DOI: 10.13005/bpj/2061
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Observational Study on Pattern of Poisoning Cases Reported to Emergency Department of a Teaching Hospital in South India

Abstract: A prospective observational study of 12 months duration was conducted in a teaching hospital on 278 cases of acute poisoning reported to emergency department from October 2018 to October 2019. Data regarding patient demographics, type of poisoning agent, duration of hospital stay and outcome were collected and analyzed. The common poisoning agents ingested were organophosphate compounds (41%), drug overdose (36%), Rodenticide (9%), House cleaning agents (6%), Mosquito repellents (4%), Corrosives (1%) and Keros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
4
1
0
Order By: Relevance
“…In our study, the majority of suspected poisoning cases were caused by the oral route (91.1%). Similar ndings have been reported by several previous studies [12,16,24]. This could be because of the easy availability of drugs that are consumed orally and used most commonly for the purpose of poisoning.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, the majority of suspected poisoning cases were caused by the oral route (91.1%). Similar ndings have been reported by several previous studies [12,16,24]. This could be because of the easy availability of drugs that are consumed orally and used most commonly for the purpose of poisoning.…”
Section: Discussionsupporting
confidence: 91%
“…Of the 146 patients, 72 (49.3%) were 21-40 years old, which was similar to the ndings of previous studies by Reddy et al [11] and Nadeem et al [12]. This nding could be because this age group is the productive age group, which is socioeconomically productive.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Acute poisoning is a major public health concern, particularly among the younger and less educated populations. 19 In our article, literature review was conducted on Pubmed, Google scholar, Dove press, Science direct etc., by using the search terms such as household poisoning, review article on household poisoning. Filters applied during the search was Year (Jan 2017-Dec 2021), Type of article (Full text review article) from which we obtained an overall of 32 full text review articles, in that 7 articles were found closely related to our review which is mentioned in Table : 2.…”
Section: Household Poisoning In Indiamentioning
confidence: 99%